The evolution of a college student - McCartney, Rhoda Claire (My University, 1905)
Introduction: The people who live in college towns and who are continually in contact with Colleges and with College people do not realize the troubles of a student coming from the decidedly rural districts. This student has not the advantages necessary for preparing him to enter College, and he is backward in his make-up, in his manner and in his general knowledge of the world. But under this outward appearance there is a true nature and an honest and upright character. The fact that his student has had but few advantages is not always due to lack of money, for on the contrary, he often comes from the homes of our wealthiest farmers. Then why is it that he is not further advanced?
Citation: McCartney, Rhoda Claire. The evolution of a college student. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Homesickness; Overwhelmed by Population and Building Size; Adopts Dress and Manners of Older Students; Theses; Manuscripts (documents)